The Image of a Russian Woman in the Modern Lithuanian Language Textbook - Čižik-Prokaševa, Veslava (Slavistica Vilnensis, 2025)
The aim of this article is to describe the image of a Russian woman in the Corpus of Contemporary Lithuanian Language. Combining a structural and cognitive approach, 1327 fiction, non-fiction and journalistic texts were analyzed. It has been established that the image of a Russian woman in these texts is presented comprehensively: Russian women are discussed in terms of physical, character, ideological, religious, social, domestic, activity, and local aspects. The physical appearance of Russians is not widely discussed, but it has been established that they do not have any distinctive features. The character, nature, behavior, and feelings of Russians are described in 232 sentences. The Corpus elaborates extensively about the activities of Russian women (405 sentences), and shows what they enjoy doing. Their social status is also richly illustrated, with the texts highlighting Russian cooperation, their recognition and appreciation (269 sentences). The Corpus examples also show that there are Russians who are less respectful of moral norms and may commit crimes. Some of the sentences show that Russian women are religious, they work hard, but are often abused. The research showed that Russian women are portrayed in texts more positively, with very few negative responses. They are most often presented as good athletes, as a person who teaches and heals others, as a person who creates and conveys art, and as amiable, kind, sincere, caring, strong women.